Performance evaluation of helium-based binary gas mixtures in standing-wave thermoacoustic electricity generator - Ikhsan Setiawan; Prastowo Murti; Irna Farikhah; Agung Bambang Setio Utomo (Results in Engineering, 2025)
This study investigates the performance of helium-based binary gas mixtures in a standing-wave thermoacoustic electricity generator (SWTAEG). The experimental setup employs a quarter-wavelength straight resonator coupled with a loudspeaker acting as a linear alternator. Four binary gas mixtures—helium-argon (He-Ar), helium-nitrogen (He-N2), helium-oxygen (He-O2), and helium-carbon dioxide (He-CO2)—were tested at varying helium molar fractions (0.0 to 1.0) under a constant working pressure of 300 kPa. Key performance metrics such as onset temperature difference ΔTonset), resonance frequency, pressure amplitude, and electrical power output were evaluated. Results show that each gas mixture exhibits a distinct optimal helium fraction where both ΔTonset is minimized and power output is maximized. Notably, the He–CO2 mixture with 0.4 helium fraction achieved the best performance, generating 1.6 W of power at the lowest ΔTonset of 229 °C. Analytical models of ΔTonset were also validated against experimental data. These findings highlight the significant influence of thermophysical properties—particularly Prandtl number and specific heat ratio—on the thermoacoustic conversion process, and demonstrate the potential of binary mixtures for optimizing energy efficiency in low-grade heat-to-electricity applications.